2021
DOI: 10.31235/osf.io/83t5n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Republicans Discriminated Against Chinese-born Americans Throughout the COVID-19 Pandemic

Abstract: Asian Americans became targets of increasingly hostile behavior during the COVID-19 pandemic. What motivated this? Fears of contagion arising from a behavioral immune system (BIS) may have motivated differential treatment towards Chinese-born US residents, especially early in the pandemic and among those vulnerable to COVID-19. On the other hand, rhetoric from right-wing media figures may have legitimated anti-Asian behavior. We explore these questions using a behavioral game with a representative sample of Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Our findings contribute to a growing body of evidence (e.g., Abascal et al 2021;He et al 2022;Lu et al 2021) suggesting that the media framing of COVID-19 as a threat from China negatively affected the treatment of Asian Americans not just in terms of high-profile physical attacks and verbal assaults but also in terms of more subtle, everyday forms of bias and discrimination (e.g., bias in financial support). By putting MTurk workers in the position of having to choose whether to forgo an amount of pay commensurate with the going rate for such work, our study has strong external validity.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Our findings contribute to a growing body of evidence (e.g., Abascal et al 2021;He et al 2022;Lu et al 2021) suggesting that the media framing of COVID-19 as a threat from China negatively affected the treatment of Asian Americans not just in terms of high-profile physical attacks and verbal assaults but also in terms of more subtle, everyday forms of bias and discrimination (e.g., bias in financial support). By putting MTurk workers in the position of having to choose whether to forgo an amount of pay commensurate with the going rate for such work, our study has strong external validity.…”
Section: Discussionsupporting
confidence: 52%
“…For example, He et al (2022) found more negative attitudes about Chinese people in U.S. locations with severer COVID-19 outbreaks. Compared to the early days in the pandemic when the outbreak was associated with China, prejudice against Asians declined when China was no longer a disease hotspot, suggesting aversive behaviors that are responsive to pathogen-threat perceptions (Abascal et al 2021). Lu et al (2021) report experimental results showing that research subjects who were primed to think about COVID-19 evaluated East Asians as well as South Asian and Hispanic individuals as less desirable hypothetical roommates than people in a control condition.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation